Passing the primary FRCA SOE : a practical guide - Blandford, Claire M., 1982- (Cambridge : Cambridge University Press, 2016)
The Structured Oral Examination can be the hardest component of the Primary FRCA examination to prepare for, but help is at hand. This book has been specifically designed to give realistic practice questions and to show you how to phrase and develop your answers. The questions included have been mapped to the FRCA examination curriculum and reflect both core and niche subject areas. Questions are presented as full mock examinations and also divided by section, enabling you to use the book in whichever way you find most effective. Complete scripted answers allow you to see how questions develop and help you to hone your technique. Handy hints and tips for exam preparation are included throughout the book, and a dedicated introduction section covers common pitfalls and how to avoid them. This is an invaluable preparation guide and sample question resource for trainees and trainers alike.
Title from publisher's bibliographic system (viewed on 05 Apr 2016).
Keywords: Anesthesiology -- Examinations -- Study guides